LABUH NYINGKAL, TRADISI BUDIDAYA PADI MASYARAKAT ADAT OSING SEBAGAI LANDASAN PENGEMBANGAN EKONOMI AGRARIS DALAM PERSPEKTIF MAQĀṢID AL-SYARĪ'AH - Hari Purnomo (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2026)
This study examines the Labuh Nyingkal tradition in the rice cultivation practices of the Osing community as a foundation for the development of an agrarian economy from the perspective of Maqāṣid al-Sharī'ah. As an indigenous agricultural tradition, Labuh Nyingkal embodies not only cultural and spiritual values but also economic principles rooted in social solidarity, environmental stewardship, and sustainable resource management. This research employs a qualitative ethnographic approach through participant observation, in-depth interviews, and document analysis to explore the meanings and practices embedded within the tradition. The collected data were analyzed using a descriptive-interpretative method by relating empirical findings to the objectives of Maqāṣid al-Sharī'ah, including the protection of religion, life, intellect, lineage, wealth, and environmental sustainability as a contemporary extension of maqāṣid. The findings reveal that Labuh Nyingkal reinforces an agrarian economic ethic that promotes collective welfare through equitable resource distribution, ecological preservation, communal cooperation, and intergenerational responsibility. Therefore, this tradition represents a viable model for strengthening a sustainable agrarian economy grounded in local wisdom while remaining consistent with the normative objectives of Maqāṣid al-Sharī'ah. Keywords : Labuh Nyingkal, Agrarian Economy, Maqāṣid al-Sharī'ah.